Hybrid flat gain C-band optical amplifier with Zr-based erbium-doped fiber and semiconductor optical amplifier - Huri, N.A.D.; Hamzah, Azura; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (IOP Publishing, 2011)
An efficient gain-flattened C-band optical amplifier is demonstrated using a hybrid configuration with a Zirconia-based Erbium-doped fibre (Zr-EDF) and a semiconductor optical amplifier (SOA). The amplifier utilizes a two-stage structure with a midway isolator to improve flat gain characteristic and reduce noise figure. At input signal power of -30 dBm, a flat gain of 28 dB is obtained from wavelength region of 1530 to 1560 nm with gain variation of less than 4 dB. The noise figure is maintained below 11 dB at the flat-gain region. This amplifier has the potential to be used in the high channel count dense wavelength division multiplexing system due to its simplicity and compact design.